LUNG CANCER SCENARIO IN SPECIFIC TERRITORIES OF INDIA AND THEIR CAUSES - F.REHMAN, (International Journal of Pharma and Bio Sciences, 2015)
Cancer is a major health problem in both developed and developing countries, second only to cardiovascular disease. Lung cancer, in particular, is a disease with high morbidity and mortality, and is a major cause of death among all types of cancers the world over( ˜ 18.2%), causing about 1.38 million deaths per year. The cause of such high mortality rate of lung cancer may be both internal (genetic, mutative, hormonal, poor immune conditions, etc ) and external (such as food habits, heavy industrialization, population explosion, life- style, smoking, etc.) Due to high death rate and ill effects of chemotherapy and radiation therapy, many cancer patients seek alternative / complementary medical treatment with milder side effects. Some natural therapies such as direct use of certain medicinal plants or the use of active ingredients extracted from these plants are reported found beneficial in combating cancer. As there exists such a wide scope of deriving potential anticancer agents from these medicinal plants, which need extensive exploration in this area. Till date only a few medicinal plants have attracted the interest of concern therapist. In view of these facts, the objective of the present article is to review the medicinal plants with antitumor potential against lung cancer, the status of lung cancer in specific territories of India and with comparison at Global level, and causes of lung cancer along with their remedial aspects, and mechanism of action.